Role of lipids, lipoproteins and lipid peroxidation in thrombocytopenia in patients with vivax malaria - Erel, O.; Kocyigit, A.; Bulut, V.; Avci, S.; Aktepe, N. (My University, 1998)
Possible roles of oxidative and metabolic changes of lipids in the development of thrombocytopenia in patients with vivax malaria were investigated. Serum total cholesterol, HDL and LDL cholesterols, triglycerides, lipid peroxidation level and platelet counts were determined in 60 patients with vivax malaria and compared with 50 healthy individuals. Inter-relationships of parameters were investigated. In patients, serum total cholesterol, HDL and LDL cholesterol concentrations and platelet counts were lower, and serum triglycerides and plasma lipid peroxidation concentrations were higher than those of control subjects. Significant relationships were found among serum lipid parameters, plasma lipid peroxidation and thrombocyte counts. Decrease in total cholesterol, HDL and LDL cholesterols and platelet counts may be related or secondary to oxidative stress. In the treatment of thrombocytopenia required in the some cases of malaria, the supplementation of antioxidative vitamins may be considered.
Keywords: Cholesterol; Lipid peroxidation; Lipids; Lipoproteins; Malaria; Thrombocytopenia